Errors in the Activation Energy and Thermal Quenching Parameters When Evaluated from Quenched Thermoluminescence Glow Peaks Using the Various Heating Rates Method. (1st April 2022) - Maghrabi, Mufeed; Al-Reyahi, Anas; Shaheen, Adel; Khattari, Ziad; Afaneh, Feras
Abstract : It is generally observed that the various heating rates (VHR) method overestimates the activation energy ( E ) when applied to quenched thermoluminescence (TL) peaks. Based on the analysis of numerically computed quenched TL peaks, we introduced an empirical expression that estimates the error in E . The expression correlates the error in E with the width of the peak, the luminescence efficiency and its first derivative at the lowest heating rate evaluated at the temperature of peak maximum. In addition, the expression accurately predicts the temperature shift of the peak maximum as a function of the heating rate. The VHR-based methods used to evaluate the quenching parameters ( W and C ) result in erroneous values. The source of error in the peak area-based method is the replacement of the unquenched peak area by the quenched peak area at the lowest heating rate as usually practiced in the literature. Accurate values of W and C were obtained when we modified the basic equation to include the luminescence efficiency at the lowest heating rate. On the other hand, we explicitly showed that the maximum intensity-based method used to evaluate these parameters is not suitable due to the lack of a reference point.